Perspectives of the Nurses to Professional Associations - Serap Altuntaş; Şeyda Yetginler (Association of Nurse Managers, 2020)
INTRODUCTION: This research was carried out to determine the views of the nurses working in Erzurum on professional associations. METHODS: This research was carried out in a descriptive and cross-sectional design with 550 nurses between March 2015 and February 2018. After the approval of the ethics committee and the permission of the institution, the research data were collected by the questionnaire and evaluated with descriptive statistical methods. RESULTS: As a result of the evaluation of the research data, it was determined that nurses think that a strong professional association is necessary but that they do not have a strong association in the profession. In addition, it was found that nurses think that existing professional associations should not be effective in solving professional problems, that a strong professional association should be formed under a new professional organization. It is determined that nurses expect their rights from professional associations, to ensure professional unity and cooperation, to solve professional problems, to achieve professionalization, to gain professional identity and to increase respectability. DISCUSSION AND CONCLUSION: As a result of the study, it was revealed that the participation rate of nurses to professional associations was not at the desired level and they had various expectations from professional associations.